Pengaruh Fixed Asset Turnover Terhadap Harga Saham Pada PT. Mayora Indah TBK - Santi Pratiwi; Nurhayati Nurhayati; Alwi Alwi (Universitas 45 Surabaya, 2023)
This research aims to determine the effect of fixed asset turnover on share prices at PT Mayora Indah, Tbk. This type of research is associative research with a quantitative approach. The population used are all financial reports in the form of balance sheets and profit and loss reports of PT. Mayora Indah, Tbk has been listed on the IDX for 45 years. The sample in this research is the financial report of PT. Mayora Indah, Tbk for 10 consecutive years, namely 2013-2022. The data collection techniques used are documentation and literature study techniques, namely by searching for information through books, journals and other literature. The data analysis used in this research is the Simple Linear Regression Test, Correlation Coefficient and Determination Test, and t Test. The research results show that there is no significant influence between fixed asset turnover on share prices at PT. Mayora Indah, Tbk.